The Role of Digital Competence and Employee Agility in Enhancing Employee Performance at the Jatiluhur Floating Net Cages - Yuda; Fadli, Uus Mohammad Darul Fadli; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
This study aims to describe digital competence, employee agility, and employee performance, as well as to analyze the effects of digital competence and employee agility-both partially and simultaneously-on employee performance at the Floating Net Cage (KJA) Zone 5 Jatiluhur. The research sample consisted of 104 field workers selected using probability sampling with a simple random sampling method. Quantitative data were collected through a Likert-scale questionnaire (1–5) and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with the assistance of SmartPLS 4. The descriptive analysis results indicate that digital competence is in the good category, employee agility is in the fairly good category, and overall employee performance is in the good category. Hypothesis testing shows that digital competence has a positive and significant effect on employee performance (t = 2.064; p = 0.040), while employee agility does not have a significant direct effect (t = 0.550; p = 0.583). However, simultaneously, digital competence and employee agility explain 65.5% of the variance in employee performance (R² = 0.655), indicating a synergistic effect in enhancing performance. Theoretically, these findings confirm digital competence as a key factor in improving work effectiveness and employees’ ability to adapt to operational and technological changes. Although employee agility is not directly significant, it functions as a reinforcing factor when combined with digital competence. Practically, this study suggests that organizations should prioritize the development of digital competence, structured agility training, and integrated strategies to optimize overall employee performance.